Freemote Emulator : A Lightweight and Visual Java Emulator for WSN - Maret, Timothée; Kummer Raphaël; Kropf, Peter; Wagen, Jean-Frédéric (My University, 2008)
Research on Wireless Sensor Networks (WSNs) has developed highly optimized software environments fitting the limited hardware resource constraints of Motes. Unfortunately, these environments suffer from relatively complex programming models. Nowadays well known languages such as Java and optimized JVMs become available and simplify the application development for the Motes. Thus, we developed the Freemote Emulator which is a Java based emulator providing a lightweight emulation tool for emerging Java based Motes. It runs experiments in real time mixing real and emulated nodes. Its layered architecture and a set of predefined code templates allow developers to quickly produce runnable code for real and emulated nodes as well as predefined scenarios to help the newcomers to introduce into the system and WSNs. Our emulator provides as well a useful visualization tool based on a parametrizable slow down feature that helps to understand complex WSN behaviours and to debug tricky implementation problems. Finally, a single emulation can run on several computers, thus allowing programmers to conduct experiments with a pretty large number of emulated and real nodes.
Keywords: Wireless Sensor Networks; Lightweight Emulator; Java Based Motes; Freemote